Community Perceptions of the Zakat Management System of the Al-Mutathahirin Mosque Council in Maliyaro Village, Ternate City : An Islamic Economic Law Perspective - Jusni Maujud; Abdul Rauf Wajo; Mustamin Gilling; Nirwan Umasugi; Zainal Abidin Marasabessy (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2026)
This study examines community perceptions of the zakat management and distribution system implemented by the Al-Mutathahirin Mosque Council in Maliyaro Village, Central Ternate District, Ternate City, from the perspective of Islamic Economic Law. This study uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observation, and documentation involving six community informants, seven mosque administrators, and representatives of the village government.The results show that the zakat management system is generally assessed positively by most community members, especially those who regularly receive zakat distribution. However, some eligible mustahik have not received their rights due to inaccuracies in data collection at the RT/RW level, which creates critical perceptions among certain informants. The zakat collected annually from three neighborhoods (RT 7, 8, and 9) reaches IDR 80–85 million and is mainly distributed in consumptive forms through coordination with neighborhood heads. From the perspective of Islamic Economic Law, the management system generally aligns with the principles of amanah (trustworthiness), justice, and territorial distribution as stated in Q.S. At-Taubah: 60. However, challenges remain in institutional formalization, transparency, separation of zakat funds from other mosque revenues, and the absence of a systematic productive zakat program. This study recommends strengthening coordination between mosque administrators and village authorities, improving data transparency, and developing productive zakat distribution models to optimize zakat as a tool for economic empowerment and poverty reduction in the community.